2018
DOI: 10.17954/amj.2018.132
|View full text |Cite
|
Sign up to set email alerts
|

SMAC Mimetiği Olarak AT-406’nın Kanserdeki Rolü

Abstract: ÖZEndojen ikinci mitokondri kökenli kaspaz aktivatörleri (SMAC), apoptozis inhibitör proteinleri (IAPs)'ni baskılayan mitokondriyal pro-apoptotik proteinlerdir. Apoptozis inhibitör proteinleri bir çok insan kanserlerinde yüksek seviyede eksprese edilmektedir. Endojen apoptosis inhibitör proteini antogonisti ikinci mitokondri kökenli kaspaz aktivatörlerini taklit eden apoptosis inhibitör proteininin küçük moleküllü inhibitörleri SMAC mimetikleri olarak adlandırılır. AT-406, XIAP'ı ve cIAP-1/2'yi etkili şekilde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In in vivo xenograft tumor studies conducted with mice, rats, dogs and nonhuman primates, DEBIO 1143 has been shown to induce apoptosis. DEBIO 1143 is currently being investigated in phase 1 clinical trials in the treatment of human cancers [5]. Our literature research demonstrated no publication related to the combined therapy of TAM and DEBIO 1143 in estrogen receptor positive breast cancer cell lines.…”
Section: Introductionmentioning
confidence: 84%
“…In in vivo xenograft tumor studies conducted with mice, rats, dogs and nonhuman primates, DEBIO 1143 has been shown to induce apoptosis. DEBIO 1143 is currently being investigated in phase 1 clinical trials in the treatment of human cancers [5]. Our literature research demonstrated no publication related to the combined therapy of TAM and DEBIO 1143 in estrogen receptor positive breast cancer cell lines.…”
Section: Introductionmentioning
confidence: 84%